11(2x-3)=5(2x+2)5

Simple and best practice solution for 11(2x-3)=5(2x+2)5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11(2x-3)=5(2x+2)5 equation:



11(2x-3)=5(2x+2)5
We move all terms to the left:
11(2x-3)-(5(2x+2)5)=0
We multiply parentheses
22x-(5(2x+2)5)-33=0
We calculate terms in parentheses: -(5(2x+2)5), so:
5(2x+2)5
We multiply parentheses
50x+50
Back to the equation:
-(50x+50)
We get rid of parentheses
22x-50x-50-33=0
We add all the numbers together, and all the variables
-28x-83=0
We move all terms containing x to the left, all other terms to the right
-28x=83
x=83/-28
x=-2+27/28

See similar equations:

| (a-18)/7=-4 | | 3x+13=x+10 | | .5=x+.66 | | 588/x=42 | | 6.8y-2.6=11 | | 6x=(x+120) | | 4x^2+84x-79=0 | | 3(3x-4)=5x | | 37=-3+5(x+6} | | 2(x+2.5)=36 | | -2.5a+6.7=-1.3 | | 2+4(2x+1)=6.25x+26 | | A=9/8(h-27) | | C(×)=13.00+0.08x | | -8.x=136 | | 7+3p=-1+6p | | 3x+2x-10=4x+20 | | -2(x-7)+9=23 | | ∆x∆¶=0 | | 9-h=-34 | | 9x-34=4x+66 | | f(6)=5*6-20 | | -x(x)=0 | | (-4/7)40=x | | 1/2x+7=x+12 | | 60=-4.54x+99.48 | | 177=74-x | | (21)/(4x)+(9)/(8)=2 | | 18-2z=14 | | 3x-103=-4x-54 | | K×1=k | | K×1=x |

Equations solver categories